The Perspectives of Plant Natural Products for Mitigation of Obesity (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The incidence of obesity has dramatically increased in recent decades, which has placed great pressure and a significant burden on people's lives and the economy. Drug treatment of obesity may have certain side effects, while surgical treatment also has risks and can cause negative emotions in people. Weight loss obtained through diet and exercise leads to a significant reduction in morbidity and mortality. Recently, there has been increasing interest in the possible beneficial effects of dietary supplements, which are products intended to "supplement" the diet. In addition to vitamins, minerals and amino acids, dietary supplements can contain herbs or other botanicals and many other ingredients. They are not drugs and are not intended to treat diseases; they are adjuvants in the management of obesity and metabolic diseases. As a consequence, there is a great need to determine specific dietary supplements for the management of obesity. This will be the content of this Special Issue.